Evaluation of Pancasila Student Profile Strengthening in Junior High Schools Using the CIPP Model - Umi Chotimah; Syarifuddin Syarifuddin; Cecil Hiltrimartin; Mariyani Mariyani; Risma Rosa Karunia (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Pancasila Student Profile Strengthening Project (PSPSP) is a core component of Indonesia's Independent Curriculum, aimed at cultivating student character and competencies grounded in Pancasila values. Despite two years of curriculum implementation, many schools have yet to fully adopt PSPSP. This study evaluated the implementation of PSPSP in one of the top-performing junior high schools in Palembang City, which adopted the program from the outset. The CIPP (Context, Input, Process, Product) evaluation model by Stufflebeam was employed. Data were collected through diagnostic analysis, interviews with school leaders and teachers, questionnaires completed by 243 students, and classroom observations. The findings indicate that PSPSP has positively contributed to students' academic growth, character development, social skills, and reflective thinking. Success was largely supported by strong stakeholder readiness and collaboration among teachers, leaders, and students. Active student engagement during PSPSP activities led to more meaningful learning experiences. To enhance program outcomes, the study recommends ongoing professional development for teachers and coordinators, as well as regular program evaluations. Sustained collaboration with parents and the broader community is crucial for long-term success. Broader national implementation strategies should consider local contexts and leverage digital tools to maximize impact. Finally, policy reinforcement is needed to institutionalize PSPSP across schools, promote school-based management, and uphold Pancasila values as the foundation of Indonesia’s educational and national development goals.